2005
DOI: 10.2190/fbnu-g3cu-jbxr-mvh6
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Systemic Retention: Implications for Improving Retention Practice in Higher Education

Abstract: Drawing on Tinto's (1987Tinto's ( , 1993 theory of student integration, this research examines students who withdrew from their original institution prior to graduation. Of this group, some of the students who withdraw do so to transfer to another institution, and it is reasonable to assume that these students are different in many ways from students who withdraw and do not continue their education. Thus, the purpose of this effort is to provide a better understanding of the characteristics of students who lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
31
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 28 publications
4
31
0
Order By: Relevance
“…Our results are consistent with these findings and are reflected in the EAPI. In particular, passes in Science and Mathematics have also been found to be a proxy for students learning ability (Lemmens, du Plessis, & Maree, 2011;Torenbeek, Jansen, & Suhre, 2013) with Mathematics contributing to success in science-related courses (Caison, 2005). Corresponding with results from other studies, our proxy indicator for academic socialisation-accommodation in a residential college-also had a significant influence for both school leavers and other students.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Our results are consistent with these findings and are reflected in the EAPI. In particular, passes in Science and Mathematics have also been found to be a proxy for students learning ability (Lemmens, du Plessis, & Maree, 2011;Torenbeek, Jansen, & Suhre, 2013) with Mathematics contributing to success in science-related courses (Caison, 2005). Corresponding with results from other studies, our proxy indicator for academic socialisation-accommodation in a residential college-also had a significant influence for both school leavers and other students.…”
Section: Discussionsupporting
confidence: 80%
“…Alternatively, academic selfefficacy prior to university study and having had some music tuition contributed positively to the index. Caison (2005), in a retrospective study, used administrative data to investigate whether retention of students was influenced by race, parental education, external work, high school GPA and first semester GPA. The results suggested that identifying key risk factors could lead to more effective interventions to improve retention.…”
Section: Studies On Predicting Academic Performancementioning
confidence: 99%
“…PINE attempts to provide an active and engaging learning environment in which students can develop, reinforce, and fine-tune their skills longitudinally. Research literature supports the importance of practice in retention [25], and if teach-back is effective for patient education [26,27], it should be effective for students, as well. In addition to traditional planned redundancy and integrative lecture progression, the student group activities and evaluative teach-back presentations should provide excellent opportunities to practice and solidify the principles and skills.…”
Section: Considerationsmentioning
confidence: 99%
“…With increased retention research, Tinto (2006) also has had a better understanding of non-residential students learning that these students must be involved in the classroom and have support when external events on the student's lives occur. Caison (2005) found that Tinto's (1975) understanding of goal commitment and student departure successfully corresponds to her own research study. She determined that a student's first year OPA is directly related to hislher goal commitment and intentions on staying in college (Caison, 2005).…”
mentioning
confidence: 53%
“…Caison (2005) found that Tinto's (1975) understanding of goal commitment and student departure successfully corresponds to her own research study. She determined that a student's first year OPA is directly related to hislher goal commitment and intentions on staying in college (Caison, 2005). Tinto (1975) determined that students' entry characteristics impact students' departure decisions.…”
mentioning
confidence: 53%